2011
DOI: 10.2528/pier11031709
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Brain Image Classification by an Improved Artificial Bee Colony Algorithm

Abstract: Abstract-Automated and accurate classification of magnetic resonance (MR) brain images is a hot topic in the field of neuroimaging. Recently many different and innovative methods have been proposed to improve upon this technology. In this study, we presented a hybrid method based on forward neural network (FNN) to classify an MR brain image as normal or abnormal. The method first employed a discrete wavelet transform to extract features from images, and then applied the technique of principle component analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 169 publications
(64 citation statements)
references
References 30 publications
1
62
0
1
Order By: Relevance
“…Therefore, it can be used as a unique feature of each landmine. PCA has been used for a wide spectrum of applications such as [49][50][51][52][53]. In this work, it is used for landmine identification.…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 99%
“…Therefore, it can be used as a unique feature of each landmine. PCA has been used for a wide spectrum of applications such as [49][50][51][52][53]. In this work, it is used for landmine identification.…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 99%
“…We compared the proposed HBP with BP [37], MBP [38], GA [39], SA [40], 2.4.1 [41], BBO [42], PSO [43], and BPSO [50] III. We compared the proposed HBP-FNN with fourteen state-of-the-art classification methods as DWT + PCA + FP-ANN [7], DWT + PCA + KNN [7], DWT + PCA + SCABC-FNN [8], DWT + PCA + SVM + HPOL [11], DWT + PCA + SVM + IPOL [11], DWT + PCA + SVM + GRB [11], WE + SWP + PNN [12], RT + PCA + LS-SVM [14], PCNN + DWT + PCA + BPNN [17], DWPT + SE + GEPSVM [18], DWPT + TE + GEPSVM [18], WE + NBC [19], WEnergy + SVM [22], and SWT + PCA + HPA-FNN [26]. IV.…”
Section: Experiments Designmentioning
confidence: 99%
“…El-Dahshan et al [7] extracted the approximation and detail coefficients of 3-level DWT, reduced the coefficients by principal component analysis (PCA), and used feed-forward back propagation artificial neural network (FP-ANN) and K-nearest neighbors (KNN) classifiers. Zhang et al [8] proposed using DWT for feature extraction, PCA for feature reduction, and FNN with scaled chaotic artificial bee colony (SCABC) as classifier. Based on it, Zhang et al [9] suggested to replace SCABC with scaled conjugate gradient (SCG) method.…”
Section: Existing Pathological Brain Detection Systemsmentioning
confidence: 99%
“…As the space inside the skull is very limited, the growth of tumour inside the skull could increase the intracranial pressure causing edema, reduced blood flow, displacement and degeneration of other tissues that control important body functions. Survival rates of the affected individual with brain tumours vary widely, depending on the type of tumour, however for brain tumour prognosis and successful treatment, therapy planning, early and accurate tumour diagnosis is imperative [1].…”
Section: Introductionmentioning
confidence: 99%